Thinking Styles and its Relationship with Self-Efficacy - Saeed Mohammed Noori Taher Bebane (Zanco Journal of Humanity Sciences)
Thinking is one of the essential cognitive processes in human's life, however the nature of its correlation with self-beliefs that an individual holds is overlapping and unclear. To clarify such overlap, also to shed lighter on the nature of interrelation between specific thinking style and self-efficacy of an individual, current study aims to investigate the correlation between thinking styles and self-efficacy by employing descriptive correlational research method among a sample of academic staff at Salahaddin University-Erbil (n = 243). To measure the current study variables, the list of thinking styles (Sternberg & Wagner 1991) used to measure thinking styles. Also, the measure of self-efficacy (Jerusalem & Schwarzer, 1986) used to measure self-efficacy. The findings indicate that there is variance in correlations between self-efficacy and thinking styles. Self-efficacy significantly correlates with legislative thinking, executive thinking, internal thinking, monarchic thinking, and liberal thinking. Whereas self-efficacy is not significantly correlated with judicial thinking, global thinking, local thinking, conservative thinking, hierarchic thinking, oligarchic thinking, anarchic thinking, and external thinking. Also, the results showed that there are differences in thinking styles according to academic ranks. Finally, current study came out with a few recommendations and suggestions.